Design and development of the front wheel hub for All-Terrain Vehicle (ATV) / Himanshu Verma...[et al.] - Verma,, Himanshu; Kumar, Sandeep; Bharj, Rabinder Singh; Kumar, Rajan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
An all-terrain vehicle (ATV) is a single seat, open cockpit, and open wheel off-road vehicle in which the engine is located behind the driver. The present paper discusses the important aspects of designing and development of the front wheel hub of ATV. This study discusses the design of the front wheel hub while considering that it should be of light weight and high strength. This paper discusses the material selection for the hub from the two different types of material. This study includes the improvement in the design of the hub with the help of various analyses of the hub. The hub is analyzed in the various loading conditions to obtain the appropriate factor of safety with the help of a static structural module of ANSYS software.